Analysis of Gravel Migration Patterns During Vibration Rolling and Their Impact on GCL Performance Based on DEM - Hu Huang; Feihao Chen; Qingming Qiu; Ruihang Li; Lixia Guo (Buildings)
In this study, a multilayer composite rolling model consisting of a rolling wheel, a protective layer, a GCL, and a support layer was constructed by the discrete element method (DEM). Soil compaction and gravel migration, and their effects on the GCL, were analyzed from a fine viewpoint, and three key indexes for the safety assessment of the GCL were proposed: local elongation, gravel embedment value, and bentonite allotment number. The results show that the soil porosity and cumulative settlement do not decrease all the time with the number of rolling passes, and there exists an optimal number of rolling passes during the rolling process; the protective layer of gravel soil moves more frequently than the support layer; and the nearly rectangular and nearly elliptical gravels are more likely to rotate. The maximum local elongation of the GCL was 3.79% during the lapping process, and all gravels in contact with the upper boundary of the GCL extruded the GCL to varying degrees during the lapping process. The distribution of bentonite particles is closely related to the contact mode between gravel and GCL.